"Nicolasa Gómez, the teacher. A biographical sketch" (2016)
A Riohachera African descent teacher devoted to wayuu children´s academic training, she provided them with literacy skills for their cultural survival. Preliminarily, methodological and theoretical elements were used to study her life. With the purpose of analyzing the context, a literature review was conducted in disciplines such as: education, history, and culture in order to establish bonds between this information and the known fragments of her work and in this way start solving both questions: Is Nicolasa´s life able to account for the history of education in the Department of La Guajira and vice versa? And, what theoretical and ideological approaches are more accurate for processing the literature consulted? The ethnographic method will get us closer to her practice and will make evident the perception of her community and the ideals that encourage her. Semi-structured interviews, files review and the preparation of a state of the art will constitute a starting point. In this exploration, we could perceive that fragments of praxis and theory ‘build’ a unit.